Early assessment as a predictor of academic performance: An analysis of the interaction between early assessment and academic performance by first-year accounting students as a South African university - Bruwer, A.; Ontong, J.M. (South African Journal of Higher Education, 2020)
Current emphasis on students’ academic adaptation in higher education necessitates the evaluation of predictors of successful preparation of first-year students. This study evaluated the implementation of early assessment (EA) in two first-year financial accounting courses at a South African university, namely an introductory financial accounting course, aimed at students without prior exposure to accounting, and a professional body accredited accounting course, aimed at students with prior exposure to accounting. This module-specific benchmark assessment, early in the academic year is often used as a predictor of preparation, adaptation and potential future academic performance. Given the discontinuation of a university, wide EA protocol within a faculty the academic contribution of the EA has been questioned. The study’s focus comprised two research questions, namely whether the EA can be used as a predictor of future academic performance of two different academic performance groups and whether students in a lower academic performance group are able to achieve success despite a low result in the EA. The research methodology included an analysis of variances to determine the correlation between the early assessment and either mid-year or final marks, as well as significance evaluation of the measured variance analysis using the Bonferroni test. The findings suggest that whilst the EA could potentially be used as an early warning sign for at-risk academically low performing students, the EA could also result in a misleading representation to students in the high academic performance category. Principally, the EA was found not to be a reliable predictor of future academic performance. In addition, the mixed results obtained from the evaluation of the effect of the nature and format of the assessment suggested that it had a low and non-meaningful effect on the predictive value of the early assessment. The fact that students in the academically low performance group were largely able to pass the module, however, suggests the success of intervention utilising the EA as an early warning. Higher education module developers could therefore consider the implementation of an appropriate EA in various undergraduate modules, based on the findings.